Content analysis of legal protection regulations for money laundering victims in Indonesia - Budiman, Arif; Munaf, Yusri; Chaidir, Ellydar; Febrianto, Surizki (International Journal of Scientific Research and Management (IJSRM), 2023)
The offense of money laundering is included within the context of corruption. Money laundering persists in evolving via many techniques, often facilitated by advancements in information technology. Consequently, a notable number of persons use these technological advancements to engage in illicit activities, including the washing of illicitly obtained funds. This research aims to analyze the development of regulations regarding the laundering crime and legal protection for victims. This research uses regulatory and statutory documents as the main data. Documents collected include laws and government regulations regarding money laundering crimes and legal protection for victims. This research uses Nvivo 12 Plus software to code documents for presentation to produce numbers in the form of images. This research found that the development of regulations relating to the crime of money laundering continues to develop so that it is no longer possible for there to be a legal vacuum. Furthermore, Indonesia has not only created legal instruments to deal with perpetrators of corruption but also provides legal protection for victims of money laundering crimes. This research only discusses the aspect of statutory documents. Future research needs a more in-depth analysis by comparing regulations and cases of money laundering crimes.